Development of diagnostic system for atherosclerosis based on intrinsic fluorescence using multispectral imaging - Ho, C.; Horiuchi, T.; Taniguchi, H.; Umetsu, A.; Hagisawa, K.; Iwaya, K.; Azmi, A.; Zulaziz, N.; Azhim, Azran; Shinomiya, N.; Morimoto, Y. (2015)
Composition of atherosclerotic arterial walls is rich in lipids such as cholesterol; unlike normal arterial walls. In this study, we aimed to utilize this difference to diagnose atherosclerosis via multispectral imaging, which allows for identification of fluorescence originating from the substance in the arterial wall. The inner surface of extracted arteries (rabbit abdominal aorta, human coronary aorta) was illuminated by an excitation light and multispectral fluorescence images were obtained. The fluorescence spectra in atherosclerotic sites were shown to be different from those in normal sites. A ratio of fluorescence intensity at a wavelength of two significant differences was then calculated for each pixel and ratio images were reconstructed. As a result, we succeeded in “disease mapping”, by which atherosclerotic sites can be discriminated from normal sites. The differences in fluorescence spectra may be attributed to the differences in fluorophores contained in the intima/media of the artery.